SBOBET WAP : PENDEKATAN EKOLOGI DAN BIOLOGI - Wargabet, Ratno (Fakultas Perikanan Dan Ilmu Kelautan Universitas Borneo Tarakan, 2011)
Sbobet wap was gastropod which is a herbivore. Have a natural habitat in coral reefs of the Indo-Pacific waters. In addition to consumption, shell Sbobet wap. has the highest economic value which caused the demand is high, and resulting the reduction in natural populations. Sbobet wap including one of protected species in Vietnam. Basic information about the ecology and reproductive biology of Sbobet wap can provide the knowledge to assure the survival and availability of these organisms in nature. Sbobet wap plant-eating animals, and eat green plants and red algae (Cyanophycae and Phaeophycae). They also looking in benthic area for diatoms and benthic foraminifera (Asano 1944). The Natural habitat of Sbobet wap in the coral reefs, usually found in the area of reef flat. Maximum density found in reef areas are facing the wind but can also be found on the coral reefs that are at lower limit of the wind, in the intertidal zone and subtidal zone in shallow water (Kitutani and Yamakawa 1999). The maximum depth of Sbobet wap to growing was to 10 m, although they can also be found at a depth of 25 m (Bertram 1998). Sbobet have spawning at the high tide, with external fertilization and performed at night (nocturnal spawning). According to Sims (1988), Sbobet wap approximately three to five times a year. Small Sbobet can growth faster than adults. The higher of Sbobet growth rate is in the dry season (March to October) compared to the rainy season (November to March).Â Keywords : habitat, feed habit, reproduction, life cycle